Amorphous film of cerium doped cobalt oxide as a highly efficient electrocatalyst for oxygen evolution reaction. Issue 13 (12th March 2019) - Xu, Shichen; Lv, Cuncai; He, Tong; Huang, Zhipeng; Zhang, Chi
Abstract : Ce doping induces structure and chemical state variation in CoO x, producing an electrocatalyst with superb performance in the oxygen evolution reaction. Abstract : The exploitation of a highly efficient electrocatalyst for the oxygen evolution reaction (OER) is urgently demanded by the wide application of clean hydrogen energy. Herein, we report the facile synthesis of an amorphous film of the cerium doped cobalt oxide (CoO x (Ce)) and its prominent performance in catalysing the OER. The film was deposited by a scalable electrostatic spray deposition method. Cerium doping induces the variation of the crystal structure of cobalt oxide from crystalline to amorphous. Meanwhile, cerium-related oxygen vacancies were introduced with cerium doping, while the chemical state of the cobalt species was unmodified. These factors lead to a drastic increase in the electrochemical surface area and the intrinsic activity of the resultant CoO x (Ce) in the OER. As a consequence, the CoO x (Ce) shows a reduced activation energy of the OER. The amorphous CoO x (Ce) film produces a current density of 20 mA cm −2 at the overpotential of 261 mV, and that of 100 mA cm −2 at 302 mV. The performance is competitive to those of the reported electrocatalysts and commercially available RuO2 .